2014
DOI: 10.5897/ijsa2014.0554
|View full text |Cite
|
Sign up to set email alerts
|

The situation of orphans and vulnerable children in selected Woredas and towns in Jimma Zone

Abstract: Orphan and vulnerable (OVC) children are children that are susceptible to various types of physiological, psychological and social problems. A qualitative research was conducted to assess the situation of orphans and vulnerable children in four woredas and two towns of Jimma Zone, Southwest Ethiopia. 21 focus group discussions and 29 key informant interviews were conducted to collect data required for the study. The data collected were analyzed using thematic analysis. The study revealed that OVC are vulnerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…4 Institutionalized children are potentially at greater risk of malnutrition. 5 A study conducted in Romania on institutionalized children has found substantial delays in cognitive development, growth, and social competence among young children who were raised in the institution. 6 The number of children who are left orphaned in the world due to the loss of parents has increased in recent years.…”
Section: Backgroundsmentioning
confidence: 99%
“…4 Institutionalized children are potentially at greater risk of malnutrition. 5 A study conducted in Romania on institutionalized children has found substantial delays in cognitive development, growth, and social competence among young children who were raised in the institution. 6 The number of children who are left orphaned in the world due to the loss of parents has increased in recent years.…”
Section: Backgroundsmentioning
confidence: 99%
“…The term "human trafficking" was initially used to describe forcing women and children into prostitution in the middle of the 20th century, along with expressions like "the trafficking in women and children" and "the trafficking in white slaves" [15] as cited in [16]. Despite its lengthy history, [17] as cited by [3] states that there is no universally agreed definition of human trafficking despite the fact that various definitions are driven and adopted by governments, NGOs, and regional authorities Its conceptual fuzziness results from the reality that human trafficking can occur in an incredibly wide range of contexts, making it difficult to write any one thorough report on the subject [18].…”
Section: Literature Review 21 Definitions Of Human Traffickingmentioning
confidence: 99%
“…More than 12% of all children in Ethiopia are affected due to the death of one or both parents due to HIV/AIDS [4]. HIV/ AIDS has changed the way millions of children are raised in Ethiopia, including Gondar, because it is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…Many are cared for by widowed or sick parents, while others live with large families [5]. In Ethiopia, about 6% of the total population, is classified as OVC [4]. According to the report of Yecokeb Berehan, there are an estimated 13,234 OVC in Gondar [6].…”
Section: Introductionmentioning
confidence: 99%